An azirine solid-state photodegradant of the CCR2/CCR5 dual antagonist BMS-813160. (9th November 2022) - Ayers, Sloan; La Cruz, Thomas; Park, Hyunsoo; Ramirez, Antonio; Hritzko, Benjamin; Sarjeant, Amy; Lin, Ziqing; Zaretsky, Serge; Huang, Yande; Zang, Jia; Yuill, Elizabeth M.; Fenster, Michaël D.B.
Graphical abstract: Abstract: The synthesis of the CCR2/5 dual chemokine antagonist BMS-813160 (1 ) presented a number of interesting impurity and degradant structure elucidation challenges. This publication will focus on the structure elucidation of the solid-state photodegradant of 1 which produced an unexpected stable azirine species. The structure was elucidated by mass spectrometry and NMR, with confirmation by single-crystal X-ray crystallography.